Methods of wintering yearling steers on bluestem pasture. - Smith, E.F.; Cox, R.F.; Fansher, S.B. (Kansas Agricultural Experiment Station, 2012)
Thirty head of good quality, about 750-pound, Hereford yearling steers were used in the test which was started December 7, 1951. The steers were purchased in the spring of 1951 and had been grazed on bluestem pasture during the summer and fall. They carried a moderate amount of flesh. They lost some flesh during October and November when they were on grass alone prior to the start of winter tests. The steers were sprayed twice with B.H.C. for lice. All of the pastures in which the steers were wintered had been grazed the previous summer at normal stocking rates but a plentiful supply or dry grass remained. From 6 to 13 acres of pasture were allowed each steer.
Keywords: Beef; Yearling steers; Bluestem pasture; Stocking rates; Protein